THE INFLUENCE OF ACID GAS LOADING ON THE PERFORMANCE OF ACID GAS ENRICHMENT (AGE) ABSORBER COLUMN - Mahdipoor, Hamid Reza (جامعة الوادي - university of el oued, 2015)
The Claus process is used to recover sulfur from acid gases and therefore, reduce environmental pollution. A lean acid gas feed containing a relatively low concentration of hydrogen sulfide lead to an unstable flame in reaction furnace and also deterioration of the catalyst in reactors due to incomplete combustion of hydrocarbons and soot or carbon deposition. Several alternatives are available to overcome this problem. Acid Gas Enrichment (AGE) is one of these methods using Amine solution to selective absorption of H2S and enrichment of acid gas. In this paper, the influence of acid gas loading in lean Amine on the performance of AGE absorber column is investigated. The achieved results shows this factor is a critical factor in the performance of selective absorption and therefore, more caution should be considered in the simulation of amine stripper
Article
Keywords: Sulfur Recovery, Acid Gas Enrichment, Selective Absorption